Influence Creativity and Discipline Student Learning Outcomes Students Against Economic Education Studies Program STKIP PGRI West Sumatra - Amelia, Fitri - (Pendidikan Ekonomi, 2014)
This study aims to analyze: 1) Against the Effects of Student Creativity Student Learning Outcomes Study Program Economics STKIP PGRI West Sumatra, 2) Effect Against Student Discipline Student Learning Outcomes Study Program Economics STKIP PGRI West Sumatra, 3) Effects of Creativity and Discipline of Students Learning outcomes students Education Program Economics STKIP PGRI West Sumatra. Time this study was conducted in September 2014 Type of research used in this study is a descriptive study associative. The population of this study there are all students Force 2011, 2012 and 2013 Economic Studies Program STKIP PGRI West Sumatra totaling 833 0rang. Data analysis techniques: descriptive analysis and inductive analysis, namely maximum likelihood test, Ramsey test, normality test, heteroscedasticity, multicollinearity test, autocorrelation test and multiple regression analysis with SPSS version 16.0. The results showed that: 1) there is a positive and significant effect of creativity on the learning outcomes of students Prodi Economic Education STKIP PGRI West Sumatra, which is indicated by the coefficient value of 0.020 based on the analysis of data obtained value t count > t table (5.837 > 1.66023) Ha acceptable means H0 is rejected, 2) there is a positive and significant impact on the outcome of student discipline student studying Economics Education Prodi STKIP PGRI West Sumatra, which is indicated by the coefficient value of 0.018 based on the analysis of data obtained value t count > t table (2.110 > 1 , 66023) means that Ha is accepted and H0 is rejected, 3) there is a positive and significant impact jointly between creativity and discipline of students on learning outcomes of students of Economic Education STKIP PGRI West Sumatra 2014/2015 based on data analysis of F > F table (144.446 > 3.087) and significant and the value of 0.000 < Î± = 0.05, reject H0 and accept Ha. This means that creativity and discipline to the student learning outcomes and the remaining 74.9 % is explained by other variables. For that to assess skilled creative in order to keep the assess skills, so with creativity and creation kekampus diligent student discipline student results better.